2019
DOI: 10.1038/s41467-018-08202-w
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic chimerism and donor-specific skin allograft tolerance after non-genotoxic CD117 antibody-drug-conjugate conditioning in MHC-mismatched allotransplantation

Abstract: Hematopoietic chimerism after allogeneic bone marrow transplantation may establish a state of donor antigen-specific tolerance. However, current allotransplantation protocols involve genotoxic conditioning which has harmful side-effects and predisposes to infection and cancer. Here we describe a non-genotoxic conditioning protocol for fully MHC-mismatched bone marrow allotransplantation in mice involving transient immunosuppression and selective depletion of recipient hematopoietic stem cells with a CD117-anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…In particular, a humanized anti-CD117 mAb, targeting HSPCs, is being explored as single-agent conditioning regimen in patients with SCID (ClinicalTrials.gov Identifier NCT02963064), and the safety and efficacy of CD117-SAP immunotoxin have been tested in preclinical studies. [17][18][19] Although targeting CD117 may open BM niches and facilitate donor stem cell engraftment, 14 this approach would not deplete more mature lymphoid cells, which may compete with donor-derived cells at later stages of T-and B-cell development. In RAG deficiency, such cells may express self-reactive specificities because of the inefficiency of negative selection and may therefore mediate immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a humanized anti-CD117 mAb, targeting HSPCs, is being explored as single-agent conditioning regimen in patients with SCID (ClinicalTrials.gov Identifier NCT02963064), and the safety and efficacy of CD117-SAP immunotoxin have been tested in preclinical studies. [17][18][19] Although targeting CD117 may open BM niches and facilitate donor stem cell engraftment, 14 this approach would not deplete more mature lymphoid cells, which may compete with donor-derived cells at later stages of T-and B-cell development. In RAG deficiency, such cells may express self-reactive specificities because of the inefficiency of negative selection and may therefore mediate immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of anti-CD117 mAb has been shown to efficiently condition immunocompetent mice, enabling the engraftment of donor cells, [14][15][16] and a clinical trial is under way in patients with SCID (ClinicalTrials.gov identifier NCT02963064). However, although CD117-SAP represents a promising nonmyeloablative agent as it depletes autologous HSPCs while preserving host immunity, [17][18][19] its use may not suffice in the context of CID-ID, in which there is a specific need to eliminate autoreactive host cells. For this reason, because of their ability to eliminate both precursor and mature hematopoietic cells (as they all express CD45), anti-CD45 mAbs represent a more attractive target for the conditioning of patients with CID-ID.…”
mentioning
confidence: 99%
“…By simultaneously targeting the stem cell compartment and malignant cells, the therapeutic goals of HSCT can hypothetically be achieved with toxicities largely confined to the hematopoietic system. Indeed, recent work in murine 17,18,22,23,25,50 , non-human primates 51,52,53 , and early human trials 54 have demonstrated feasibility and limited toxicities of antibody and ADC-based therapies alongside high efficacy in depleting recipient HSCs and/or malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, acute rejection seriously impedes the application of skin transplantation, and inducing immune tolerance to allogeneic skin grafts is more difficult compared to solid organ transplants. Therefore, reliable strategies are necessary in order to inhibit rejection and minimize complications in allogeneic skin transplantation …”
Section: Discussionmentioning
confidence: 99%